Synthesis and Characterization of TiO2-Water Nanofluids - Raviteja Surakasi; Srujana Sripathi; Sarada Purnima Nadimpalli; Sibtain Afzal; Bharat Singh; Manoj Tripathi; Rahel Alemu Hafa (Adsorption Science & Technology)
Nanofluids made of TiO2 and multiwalled carbon nanotubes are the focus of our study. Using TiO2 and water as the basic fluids, nanofluids were created in 100 : 0, 75 : 25, and 50 : 50 proportions. Carbon nanotubes (CNTs) were disseminated into these base fluids of three types at 0.125, 0.25, and 0.5 percentages. Over the course of two months, the change of zeta potential is monitored to assess the stability of the dispersion. XRD analysis and SEM and TEM analysis are carried out for TiO2 nanofluids. Nanoparticles were analyzed using EDAX analysis to identify their composition. SEM examination was used to investigate the morphology for TiO2 nanoparticles. Particles of TiO2 produced in this manner seemed to have an average diameter of 27 nm. Nanofluids have a poor stability, which is the most important aspect of employing them, although most studies did not focus on this. When it comes to nanofluids, this study is unique in that it provides an in-depth look of surface modification approaches that have been employed by researchers to address these issues, as well as an evaluation of their stability over two months. Solubility is improved by acid treatment of CNTs, which results in functional groups on the surface of CNTs.